TO OPTIMIZATION OF AIR TRAFFIC CONTROL BY VISUAL-COGNITIVE COMPONENT DEVELOPMENT - G. A. Kryzhanovskij; K. Yu. Ponomarev; M. V. Timoshko (Научный вестник МГТУ ГА)
The article deals with the development of visual-cognitive component in interaction of the air traffic service specialist with the colour-graphic interface (of the information environment for monitoring the dynamic air situation) of a typical automated air traffic control system. Some weak points were found through monitoring of the air traffic controller interaction with information environment of interface. Elimination of the revealed drawbacks contributes to the most rational functional condition of air traffic control system. It becomes extremely important in high workload periods and especially in the situations of sharp urgency, e.g. in a shortterm conflicts, in hazardous meteorological conditions, in unforeseen or emergency situations in flight etc. The way of optimization of the air traffic control in the automated system is examined by applying visually-cognitive aids (tools) of user interaction available nowadays with the colour-graphic interface of the information environment. In a sense, we can talk about developing a cognitive support system for making rational decisions to identify potentially conflict situations and to counteract latent type of such situations. The development of decision support tools of rational orientation requires an analysis of the activity of the decision-maker, taking into account his personal factor, where the joint explication of the personal factor with information provision is appropriate. In this connection, the key priority is the development of information provision with colour-chromatic supplement of labels and aircraft marks. It results in information reduction to the minimum necessary and sufficient for making a decision on a rational basis. Application effect of the developed visual-cognitive solutions in the real route air traffic controllers test group is presented.